Caracterização de produtos panificados à base de féculas de mandioca nativas e modificadas - Aplevicz, Krischina Singer (2006)
Cassava starch is used as the main ingredient for making biscuits and cheese bread. Sour cassava starch is produced without an established standard of quality, with hygiene problems in processing, as well as product availability during the years. Still the production technology is not standardized, as well as the characterization of this product. This study has the objective of characterizing baked products with native and modified cassava starches for baked foods and tests a new formulation including the byproduct okara. In this work, commercial samples of cheese bread, cassava starch biscuits, chipa paraguaya as well as cassava starch, sour cassava starch and modified cassava starches were compared in terms of physicochemical properties. The quality characteristics of cheese bread, cassava starch biscuits and cheese bread supplemented with 5, 10 and 15% of okara were investigated. The characteristics of sour starch that makes it different from cassava starch are pH, acidity, degree of expansion, viscosity, clarity of the starch paste, freeze-thaw stability and reducing power. Four different starches were applied in the production of the baked products: cassava starch, sour cassava starch, starch modified with hydrogen peroxide and the modified starch named ExpandexÒ 160003. The baked products were evaluated in order to establish their physicochemical properties and observe the influence of the different starches on sensory evaluation. The results showed that the cheese breads supplemented with the byproduct okara had an increase in the protein and dietary fiber contents. The baked foods were submitted to an acceptability sensory evaluation with a nine point hedonic scale, involving untrained panelists. For the cheese bread samples containing sour starch cassava, starch modified by oxidation with hydrogen peroxide and the commercial starch ExpandexÒ 160003 resulted in close acceptability. For the cassava starch biscuits it was possible to conclude that the sour cassava starch and ExpandexÒ 160003 did not differ statistically. The cheese breads made with 5, 10 and 15% of okara were not statistically different at the level 5% and had good acceptability.